Side-firing intraoperative ultrasound applied to resection of pituitary macroadenomas and giant adenomas: A single-center retrospective case-control study - Baker, Katherine E.; Robbins, Austin C.; Wasson, Robert G.; McCandless, Martin G.; Lirette, Seth T.; Kimball, Rebekah J.; Washington, Chad W.; Luzardo, Gustavo D.; Stringer, Scott P.; Zachariah, Marcus A. (Frontiers in Oncology, 2022)
Introduction Multiple intraoperative navigation and imaging modalities are currently available as an adjunct to endoscopic transsphenoidal resection of pituitary adenomas, including intraoperative CT and MRI, fluorescence guidance, and neuronavigation. However, these imaging techniques have several limitations, including intraoperative tissue shift, lack of availability in some centers, and the increased cost and time associated with their use. The side-firing intraoperative ultrasound (IOUS) probe is a relatively new technology in endoscopic endonasal surgery that may help overcome these obstacles. Methods A retrospective analysis was performed on patients admitted for resection of pituitary adenomas by a single surgeon at the University of Mississippi Medical Center. The control (non-US) group consisted of twelve (n=12) patients who received surgery without IOUS guidance, and the IOUS group was composed of fifteen (n=15) patients who underwent IOUS-guided surgery. Outcome measures used to assess the side-firing IOUS were the extent of tumor resection, postoperative complications, length of hospital stay (LOS) in days, operative time, and self-reported surgeon confidence in estimating the extent of resection intraoperatively. Results Preoperative data analysis showed no significant differences in patient demographics or presenting symptoms between the two groups. Postoperative data revealed no significant difference in the rate of gross total resection between the groups (p = 0.716). Compared to the non-US group, surgeon confidence was significantly higher (p < 0.001), and operative time was significantly lower for the US group in univariate analysis (p = 0.011). Multivariate analysis accounting for tumor size, surgeon confidence, and operative time confirmed these findings. Interestingly, we noted a trend for a lower incidence of postoperative diabetes insipidus in the US group, although this did not quite reach our threshold for statistical significance. Conclusion Incorporating IOUS as an aid for endonasal resection of pituitary adenomas provides real-time image guidance that increases surgeon confidence in intraoperative assessment of the extent of resection and decreases operative time without posing additional risk to the patient. Additionally, we identified a trend for reduced diabetes insipidus with IOUS.